\[\boxed{\text{737\ (737).\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[x + y = 6;\ \ \ \ \ \text{xy} = - 3\]
\[1)\ x³y² + x²y³ =\]
\[= x^{2}y^{2}(x + y) = ( - 3)^{2} \cdot 6 =\]
\[= 9 \cdot 6 = 54\]
\[2)\ (x - y)^{2} = x² - 2xy + y^{2} =\]
\[= x^{2} + 2yx + y^{2} - 4xy =\]
\[= (x + y)^{2} - 4xy =\]
\[= 6^{2} - 4 \cdot ( - 3) = 36 + 12 = 48\]
\[3)\ x^{4} + y^{4} =\]
\[= x^{4} + y^{4} + 2x^{2}y^{2} - 2x^{2}y^{2} =\]
\[= \left( x^{2} + y^{2} \right)^{2} - 2x^{2}y^{2} =\]
\[= \left( x^{2} + y^{2} \right)^{2} - 2 \cdot 9 =\]
\[= \left( x^{2} + y^{2} \right)^{2} - 18 =\]
\[= \left( x^{2} + y^{2} + 2xy - 2xy \right)^{2} - 18 =\]
\[= \left( x^{2} + y^{2} + 2xy - 2 \cdot ( - 3) \right)^{2} - 18 =\]
\[= \left( (x + y)^{2} + 6 \right)^{2} - 18 =\]
\[= \left( 6^{2} + 6 \right)^{2} - 18 =\]
\[= (36 + 6)^{2} - 18 = 42^{2} - 18 =\]
\[= 1764 - 18 = 1746\]
\[\boxed{\text{737.\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[(2a - 3x)^{2} + (x - 1)^{2} =\]
\[= 10 \cdot (x - 2)(x + 2)\]
\[4a^{2} - 12ax + 9x^{2} + x^{2} - 2x + 1 =\]
\[= 10 \cdot \left( x^{2} - 4 \right)\]
\[- 2x - 12ax = - 4a^{2} - 41\]
\[- 2x \cdot (1 + 6a) = - 4a^{2} - 41\]
\[1 + 6a = 0\]
\[6a = - 1\ \ \]
\[a = - \frac{1}{6}\]
\[при\ \ a = - \frac{1}{6}\ уравнение\ \]
\[не\ имеет\ корней:\]
\[4 \cdot \left( - \frac{1}{6} \right) - 12x \cdot \left( - \frac{1}{6} \right) - 2x =\]
\[= - 41\]
\[- \frac{2}{3} + 2x - 2x = - 41\]
\[0x = - 41 + \frac{2}{3}\]
\[0 \neq - 40\frac{1}{3}\]
\[Ответ:\ при\ a = - \frac{1}{6}.\]